(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2014)
Computer science is a continuously evolving field. In addition to learning theoretical foundations, students of computer scienceshould keep abreast of latest trends and developments in technology happening globally to stay ahead in the field. Though classroom learning and peer interaction has no substitute, but online web resources are important learning component to transform astudent into a practically skilled engineer. Thousands of websites are available boasting of expert guidance in computer science,but students generally end up wasting precious time browsing irrelevant sites. This paper presents a collection of 15 best websitesmeant for undergraduate students to use along with traditional college education for overall professional development